Bancos comunitarios de semillas: concepto y practica. Manual para el facilitador - Vernooy, Ronnie; Sthapit, B.R.; Bessette, Guy (Bioversity International, 2018)
Over three decades, a number of international and national organizations have provided technical and financial support to community seed banks around the world. Only a few of these organizations have developed and published a practical guide about how they have offered this support. This handbook fills the gap and advances research and capacity development regarding community seed banks. The handbook is organized as a guide for facilitators — people who work in the field with farmers and their organizations on issues of seed conservation and sustainable use. The publication Community seed banks: origins, evolution, and prospects edited by Ronnie Vernooy, Pitambar Shrestha, and Bhuwon Sthapit (Vernooy et al. 2015), which offers a global overview of diverse community seed banks around the world, provided the foundation for the content of this handbook. Parts of that publication have been updated and integrated into the handbook.